Relations of coral reef benthos composition and horseshoe crabs’ gut content - Md Razak, Mohd Razali; Kassim, Zaleha; Sabuti, Asnor Azrin (2023)
Intensive earlier studies on horseshoe crab feeding ecology are focused on the Atlantic species, Limulus polyphemus (Linnaeus, 1758). However, the distribution of species, food abundance, and availability of benthos in a particular environment might influence the horseshoe crab's preference for diet in a particular region. The aims of this research are to analyse the benthos composition in Tachypleus gigas spawning site and coral reefs located near the spawning ground in Cherok Paloh, Pahang, and compare it with the food composition inside the T. gigas digestive track. A total of 30 samples of male and female horseshoe crabs, T. gigas respectively, were harvested by using a fishing net during the incoming high tide. Their guts were dissected, and the contents were analysed according to Squires and Dawe criteria. Results showed that echinoderm was the main food composition in the gut of males (54.27%) and females (51.44%) during the open sea migration phase. Amuk-amuk coral reef (3°41'51"N 103°24'13"E), Raja Muda coral reef (3°38'01"N 103°28'23"E) and Air Leleh coral reef (3°35'38"N 103°29'00"E) are the nearest sea urchin habitats to the sampling area. Benthos analysis showed higher echinoderm composition in those coral reefs (31.58 – 42.11%). There is no echinoderm composition found in the spawning site sediment. Further study is needed to provide reliable data on the significance of coral reefs in the horseshoe crab's foraging ecology.